Manuscrit de base et variantes de tradition dans le Chevalier de la charrette - Stefano Asperti; Caterina Menichetti; Maria Teresa Rachetta (Perspectives Médiévales)
In the last decades, thanks to the development of new technologies, scholars have been provided with a large amount of digital resources and data. For Chrétien de Troyes’ Conte de la charrette, such an improvement is mainly due to the homonymous Project developed by Foulet and Uitti, and to its various continuations. However, such resources have had little impact on the discussion concerning textual criticism, in the context of the vivid debate about the Copie Guyot (BNF, fr. 794), the manuscrit-de-base (guide-manuscript) of all the recent editions of the roman. We propose to broach the problem in a new fashion, in order to highlight the rich heritage of variant readings of the manuscripts and to preserve the readability of the text. Therefore, the reader will find in this article a critical presentation of the text accompanied with a commentary on the varia lectio connected to the “base-version”. Such a purpose shall be exemplified with the study of five specific excerpts, the variant readings of which will be reassessed here. This enables us to shed a new light on the text by Chrétien de Troyes, from a lexical, linguistic and definitely literary point of view.